Efecto de diferentes dosis de fitohormona Cerone sobre el proceso de maduración en la variedad de Piña MD-2 o Golden Sweet en la zona de Quevedo. - Franco Castillo, Brian Lagener (2017)
The present work was carried out in the property of the Tierra Verde hacienda of the company, Piñas Ricas del Ecuador S.A. "PIRECUASA", located in Canton Quevedo, its geographical coordinates are 1 ° 48'30.84 "south latitude and 79 ° 43'77.76" west longitude. The general objective of the present study was to study the effect of different doses of Cerone phytohormone on the maturation process of pineapple (Ananas comosus L.) MD-2 or Golden Sweet, and the specific objectives were: 1: to evaluate different dose of ethylene applied pre-harvest in pineapple fruits in the variety MD-2 or Golden Sweet to achieve desired organoleptic characteristics, 2: to determine the internal and external quality of the pineapple fruits of the variety MD-2 in relation to the doses applied, 3: carry out the economic analysis of the performance level according to the cost of the treatments | The piña variety studied was MD-2, which corresponded to the treatments under study in the Quevedo area. For this area, the experimental Randomized Complete Block Design (RCBD) with three replications was used. The Tukey test was applied to 95% to evaluate the external characteristics and Student's t-test for the internal characteristics and to establish the statistical differences between the means of the variables to determine the statistical differences. The variables color index, fruit height, fruit weight, fruit translucency, pulp content (%), degrees ° Brix (SSC), acidity (pH) and citric acidity were evaluated. Based on the interpretation and analysis of the results, it was concluded that the treatments did not show significant variations during the maturation process, indicating that for MD-2 the correct dose is determined according to the target market. The dose of 400ml/200l per hectare in a single application, is the treatment that presented the best quality both external and internal, considering a stable and uniform development of maturation. Key Words: Pineapple, ripening, quality, cerone and harvest